Moments of vision and miscellaneous verses - Hardy, Thomas, 1840-1928 (Hardy, Thomas, 1840-1928. Poems (Ryburn), 2013)
The text for this volume of poetry reproduces the first edition of 1917, allowing Hardy's poems to be read as he first gathered them and as the publishers first produced them. This edition also contains an introduction and a bibliography.